1991
DOI: 10.1002/jat.2550110403
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning by Gyromitra esculenta–a review

Abstract: Gyromitra esculenta (Pers.: Fr.) Fr. and a few other mushrooms have caused severe poisonings and even deaths in humans. Clinical data are characterized primarily by vomiting and diarrhoea, followed by jaundice, convulsions and coma. Gastrointestinal disorders distinguish this poisoning. Frequent consumption can cause hepatitis and neurological diseases. The species of concern are mainly G. esculenta and G. gigas (Kromb.) Cooke (non Phill.). Nevertheless, recent advances in chromatography, biochemistry and toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
51
0
5

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 58 publications
0
51
0
5
Order By: Relevance
“…Symptoms begin 4-12 h after ingestion. Clinical progression is vomiting and diarrhea followed by neurological symptoms (vertigo, ataxia, nystagmus, tremor, convulsions, and coma) [2,29,30,42]. Hepatic necrosis, methemoglobinemia, hemolysis and rhabdomyolysis are also reported.…”
Section: Epileptogenic Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms begin 4-12 h after ingestion. Clinical progression is vomiting and diarrhea followed by neurological symptoms (vertigo, ataxia, nystagmus, tremor, convulsions, and coma) [2,29,30,42]. Hepatic necrosis, methemoglobinemia, hemolysis and rhabdomyolysis are also reported.…”
Section: Epileptogenic Syndromesmentioning
confidence: 99%
“…Hepatic necrosis, methemoglobinemia, hemolysis and rhabdomyolysis are also reported. Jaundice may be noted [30,33,[42][43][44]. Approximately 10 % of patients poisoned will die [42].…”
Section: Epileptogenic Syndromesmentioning
confidence: 99%
“…Agaritine from the commercial mushroom Agaricus bisporus and its relatives was the first natural hydrazide to be discovered (6). The false morel Gyromitra esculenta poisons foods and causes Gyromitra syndrome, probably via the toxic hydrazide gyromitrin and its degradation products, N-formyl-N-methylhydrazine and methylhydrazine (7). Other fungi and actinomycetes bacteria produce hydrazides that have potential antibiotic, antiviral, anticancer, and antioxidant properties (5).…”
mentioning
confidence: 99%
“…One example is the hemolytic toxin gyromitrin, which is produced by false morel mushrooms (9). An alkaloid containing a hydrazone has also been isolated from a marine sponge (18).…”
mentioning
confidence: 99%
“…Hydrazones also involve many chiral building blocks, and they are applied in the agrochemical, pharmaceutical, and chemical industries (15). Hydrazones with replacement of R 2 and R 3 with hydrogen atoms, as used herein, involve many synthetic and natural compounds (9,15,18), but most of their physiological roles and biosynthetic mechanisms are unknown. We recently found that the yeast Candida palmioleophila MK883 produces hydrazone dehydrogenase (HDH) and assimilates hydrazones, such as adipic acid bis(ethylidene hydrazide) (AEH) and valeric acid ethylidene hydrazide (VEH) (3).…”
mentioning
confidence: 99%